Dichlorosilylene Transfer to a P‐Fluorophosphaalkene: The Route to a C‐Dichlorofluorosilyl‐Functionalized Dialkyldiphosphene. Issue 11 (23rd March 2017) - Mitrofan, Cristina; Gust, Thorsten; Zanin, Andreas; Bîrzoi, Roxana M.; Jones, Peter G.; du Mont, Wolf‐W.; Hayashi, Satoko; Nakanishi, Waro; Marsmann, Heinrich C.
Abstract : Reactions of the (trichlorosilyl)germane Me3 GeSiCl3 and of the unsymmetric disilane Me3 SiSiCl3 with the P ‐fluorophosphaalkene (Me3 Si)2 C=PF (1 ) proceed with transfer of SiCl2 (2 ) leading to the new C ‐dichlorofluorosilyl‐functionalized dialkyldiphosphene (Cl2 FSi)(Me3 Si)2 CP=PC(SiCl2 F)(SiMe3 )2 (6 ), which was characterized by X‐ray crystallography. The P ‐phosphanylphosphaalkene (Me3 Si)2 C=PP[C(SiCl2 F)(SiMe3 )2 ]SiCl2 F (8a ) was detected in the reaction mixtures by 31 P NMR spectroscopy, accompanied by its isomer8b, presumably (Cl2 FSi)(Me3 Si)C=PP[C(SiCl2 F)(SiMe3 )2 ]SiMe3 . The unsymmetric dimers8a and8b rearrange by a 1, 3‐(P→C) silyl group shift, providing the inversion‐symmetric diphosphene6 . Compound6 was transformed with selenium into a selenadiphosphirane (9 ). Quantum chemical calculations were performed on intermediates on the route from1 and2 to the metastable unsymmetric dimers8a and8b . The addition of SiCl2 to the P=C bond of1, followed by ring opening of the silaphosphirane4, provides the phosphinidene (Me3 Si)2 (Cl2 FSi)CP (5 ), which rearranges further to isomeric P ‐silylphosphaalkenes (Me3 Si)2 C=PSiCl2 F (7a ) and (Cl2 FSi)(Me3 Si)C=PSiMe3 (7b ). Rapid phosphinidene–phosphaalkene P–P coupling reactions of5 with7a and with7b followed by 1, 2‐(P→P) silyl group shift of ylide‐type dimers11a and11b explain the formation of the observed species8a and8b . The absence of species related to8b in previous experiments on the reactions of the P ‐chlorophosphaalkene (Me3 Si)2 C=PCl (1′ ) with Si2 Cl6, with Me3 GeSiCl3, and with Me3 SiSiCl3, allows us to suggest that in the P ‐chlorophosphaalkene case nucleophile‐supported SiCl2 insertion into the P–Cl bond or the substitutive Cl – /SiCl3 – exchange are the preferred routes to the metastable P ‐(trichlorosilyl)phosphaalkene (Me3 Si)2 C=PSiCl3 . Abstract : SiCl2 transfer from Me3 MSiCl3 (M = Si, Ge) to the fluorophosphaalkene1 provides the diphosphene6 . En route to the isomeric intermediates8a and8b, observed by 31 P NMR spectroscopy, are, according to DFT calculations, a transient silaphosphirane, the phosphinidene (Cl2 FSi)(Me3 Si)2 CP (5 ), and the isomeric P ‐silylphosphaalkenes (Me3 Si)2 C=PSiCl2 F (7a ) and (Cl2 FSi)(Me3 Si)C=PSiMe3 (7b ), which undergo P–P coupling with5 .